Personeelontwikkeling: Programbeplanning - M.V. Vermaak (AOSIS, 1982)
A well-planned, comprehensive program for the development of nursing staff in a hospital or other health service can make a significant contribution to the quality of nursing care and the intrinsic motivation of the nursing staff. Terms connected with staff development are clarified, a framework for planning a staff development program is suggested, and factors to be considered in the planning process are highlighted.